2.4 Å resolution crystal structure of human TRAP1NM, the Hsp90 paralog in the mitochondrial matrix. Issue 8 (4th August 2016) - Sung, Nuri; Lee, Jungsoon; Kim, Ji-Hyun; Chang, Changsoo; Tsai, Francis T. F.; Lee, Sukyeong
Abstract : The 2.4 Å resolution crystal structure of human mitochondrial TRAP1NM is reported, which together with epitope‐mapping results supports a role for the M‐domain in mediating the specific interaction with mitochondrial Hsp70 that is required for TRAP1‐dependent protein folding. Abstract : TRAP1 is an organelle‐specific Hsp90 paralog that is essential for neoplastic growth. As a member of the Hsp90 family, TRAP1 is presumed to be a general chaperone facilitating the late‐stage folding of Hsp90 client proteins in the mitochondrial matrix. Interestingly, TRAP1 cannot replace cytosolic Hsp90 in protein folding, and none of the known Hsp90 co‐chaperones are found in mitochondria. Thus, the three‐dimensional structure of TRAP1 must feature regulatory elements that are essential to the ATPase activity and chaperone function of TRAP1. Here, the crystal structure of a human TRAP1NM dimer is presented, featuring an intact N‐domain and M‐domain structure, bound to adenosine 5′‐β, γ‐imidotriphosphate (ADPNP). The crystal structure together with epitope‐mapping results shows that the TRAP1 M‐domain loop 1 contacts the neighboring subunit and forms a previously unobserved third dimer interface that mediates the specific interaction with mitochondrial Hsp70.